Optical film, and display member and display device using the same

JP7635364B2Active Publication Date: 2025-02-25TOPPAN TOMOEGAWA OPTICAL FILM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023507062
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-16
Filing Date
2022-03-11
Publication Date
2025-02-25
Estimated Expiration
2042-03-11

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、高屈曲性と高硬度とを両立し、カールが低減された光学フィルムを提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635364000002
    Figure 0007635364000002
  • Figure 0007635364000003
    Figure 0007635364000003
  • Figure 0007635364000004
    Figure 0007635364000004
Patent Text Reader

Abstract

Provided is an optical film that exhibits both high flexibility and high hardness, and has reduced curl. An optical film in which a hard coat layer is layered on a polyimide substrate, wherein the hard coat layer comprises a cured film of a polysiloxane having a cation-polymerizable organic functional group, and when the optical film is cut into a rectangular shape having short sides 50 mm in length parallel to the flow direction and long sides 150 mm in length parallel to the width direction orthogonal to the flow direction, and the cut sample is mounted on a flat surface, the average value of the distance between the ends of one short side and the distance between the ends of the other short side is 18 mm or greater.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical film for protecting a screen, and a display member and a display device using the same. [Background technology]

[0002] Some mobile terminals such as smartphones are provided with a protective cover glass on the display screen. For example, Patent Document 1 describes a cover glass having a thickness of 0.3 to 1.5 mm that is formed by subjecting a substrate such as an aluminosilicate glass to a chemical strengthening treatment. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 5881414 Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, in order to achieve both a larger display screen and a smaller device size, mobile terminals with foldable display screens have been developed. In order to make the display screen foldable, each member constituting the display device must be foldable. Therefore, various protective films using a resin film as a base material have been considered as a replacement for the cover glass provided on the outermost surface.

[0005] Although the resin film has flexibility, its surface hardness is inferior to that of glass, so it is necessary to provide a hard coat layer on the surface of the resin film to compensate for the hardness. However, there is room for further consideration in order to achieve both the flexibility required for a foldable display device and the hardness required for a protective film. In addition, a film having a cured resin layer such as a hard coat layer on a substrate is prone to curling. It is desirable for the curl to be small so as not to impair the machine suitability during film production and the processability in the subsequent steps.

[0006] Therefore, an object of the present invention is to provide an optical film that has both high flexibility and high hardness and is reduced in curl. [Means for solving the problem]

[0007] The present invention relates to an optical film having a structure in which a hard coat layer is laminated on a polyimide substrate. (However, this does not include those that contain layers other than these two layers.) wherein the hard coat layer is made of a cured film of a composition containing a resin component and a polymerization initiator (excluding those containing a cured product of a (meth)acrylate compound), the resin component is made of a polysiloxane having a 2-(3,4-epoxy)cyclohexylethyl group and does not contain any polymerizable component other than the polysiloxane having a 2-(3,4-epoxy)cyclohexylethyl group, the polymerization initiator is a thermal cationic polymerization initiator or a photo cationic polymerization initiator, the thickness of the substrate is 50 to 80 μm, the thickness of the hard coat layer is 5 to 30 μm, and when the optical film is cut into a rectangle having a short side of 50 mm and a long side of 150 mm, and the cut sample is placed on a flat surface, the average value of the distance between both ends of one short side and the distance between both ends of the other short side is 18 mm or more.

[0008] A display member and a display device according to the present invention include the above optical film. Effect of the Invention

[0009] According to the present invention, it is possible to provide an optical film which has both high flexibility and high hardness and is reduced in curl. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic configuration of a display device according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing a layer structure of the optical film shown in FIG. [Diagram 3] FIG. 3 is an explanatory diagram of a method for measuring curl of an optical film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] FIG. 1 is a cross-sectional view showing a schematic configuration of a display device according to an embodiment, and FIG. 2 is a cross-sectional view showing a layer configuration of an optical film shown in FIG.

[0012] The display device 10 includes a circular polarizer 3, a resin film 2, and an optical film 1 in this order on the display surface side of the display panel 4. A self-luminous panel such as an organic EL panel or a micro LED can be suitably used as the display panel 4. The circular polarizer 3 is composed of a linear polarizer and a quarter-wave plate, and is provided to suppress reflection of the outer periphery of light incident on the display panel 4. The resin film 2 is provided, for example, to improve the hardness of the surface of the display device 10. The material of the resin film 2 is not particularly limited, but for example, polyimide can be suitably used. However, the resin film 2 may be omitted.

[0013] The display panel 4, the circular polarizer 3, the resin film 2, and the optical film 1 constituting the display device 10 are all configured using a resin film as a base material, and the display device 10 is foldable. By attaching the foldable display device 10 to a main body configured to be foldable via a hinge, a foldable mobile terminal can be configured.

[0014] The optical film 1 is a protective film provided on the outermost surface of a display device 10, and serves as a substitute for the function of a cover glass. As shown in Fig. 2, the optical film 1 is formed by laminating a hard coat layer 6 on one surface of a substrate 5, and has flexibility.

[0015] The substrate 5 is a transparent polyimide film, and has durability against repeated folding due to the excellent mechanical strength of polyimide. The thickness of the substrate 5 is not particularly limited, but is preferably 20 to 80 μm.

[0016] The hard coat layer 6 is a functional layer for imparting hardness to the optical film 1. The hard coat layer 6 is made of a cured film obtained by cationic polymerization of polysiloxane having a cationic polymerizable organic functional group and a siloxane bond. The optical film 1 according to this embodiment is used as a protective film for a foldable display device 10, and therefore the hard coat layer 6 needs to have both hardness and flexibility.

[0017] Here, when the hard coat layer is formed from a polymerizable organic compound, it is possible to obtain an optical film having flexibility, but the hardness of the hard coat layer is likely to be insufficient. If the thickness of the hard coat layer is increased to compensate for the hardness, the hard coat layer is likely to crack when folded, resulting in a decrease in flexibility, and the curl of the obtained optical film is large, increasing the possibility of defects occurring in the manufacturing process of the optical film. Therefore, when the hard coat layer is formed from a polymerizable organic compound, it is difficult to obtain an optical film having surface hardness, flexibility, and low curl. In addition, when the hard coat layer is formed from an inorganic compound, the surface hardness is high, but the hard coat layer is likely to crack and flexibility is not obtained.

[0018] In this embodiment, the hard coat layer 6 is formed from an organic-inorganic composite material having a cationically polymerizable organic functional group and a siloxane bond. Therefore, the organic structural portion in which the organic functional groups are polymerized together exhibits the flexibility required for bending, and the inorganic structural portion consisting of the siloxane bond exhibits the hardness required for a protective film.

[0019] Polysiloxane is an oligomer having a siloxane bond as a skeleton, and has as its constituent units an M unit having three organic functional groups bonded to a silicon atom, a D unit having two organic functional groups bonded to a silicon atom, a T unit having one organic functional group bonded to a silicon atom, and a Q unit having no organic functional group bonded to a silicon atom. For example, a polysiloxane having a network structure including a T unit can be used as a material for forming the hard coat layer 6 according to this embodiment. For example, the cationic polymerizable organic functional group of polysiloxane can be a cyclic ether group or a vinyl group, such as a glycidyl group such as a 3-glycidoxypropyl group, or an alicyclic epoxy group such as a 2-(3,4 epoxy)cyclohexylethyl group.

[0020] The hard coat layer 6 can be formed by applying a coating liquid containing a polysiloxane having a cationic polymerizable organic functional group and a thermal cationic polymerization initiator or a photo-cationic polymerization initiator to a polyimide substrate 5, and curing the coating film by heating or irradiating with light (ultraviolet rays). The coating liquid for forming the hard coat layer may contain a solvent, a curing accelerator, and other additives as necessary. In radical polymerization, the polymerization reaction proceeds rapidly, so curling is likely to occur as the coating film hardens. If the optical film 1 curls too much, the mechanical suitability in the manufacturing process of the optical film deteriorates, and problems such as breakage may occur. In addition, if the optical film 1 curls too much, problems may occur when the film is attached to a circularly polarizing plate. When the hard coat layer 6 is cured by cationic polymerization, the polymerization reaction proceeds slowly, but curling can be suppressed.

[0021] FIG. 3 is an explanatory diagram of a method for measuring curl of an optical film.

[0022] First, the optical film 1 according to this embodiment is cut into a rectangle having a short side of 50 mm parallel to the machine direction (MD) and a long side of 150 mm parallel to the width direction (TD) perpendicular to the machine direction. Next, the cut sample is placed on a flat surface (on clean paper laid on a flat workbench) as shown in FIG. 3. The optical film 1 according to this embodiment has an average value of the distance A between both ends of one short side and the distance B between both ends of the other short side of 18 mm or more. If the average value of the distances A and B is 18 mm or more, curling is suppressed, and the influence of curling in the manufacturing process of the optical film 1 and the manufacturing process of the display device 10 can be reduced. If the average value of the distances A and B is less than 18 mm, the cut sample curls so much that it curls into a cylindrical shape, and the machine suitability in the manufacturing process of the optical film 1 and the manufacturing process of the display device 10 deteriorates.

[0023] The thickness of the hard coat layer 6 (after curing) is preferably 5 to 30 μm. If the thickness of the hard coat layer 6 is less than 5 μm, the surface hardness may be insufficient. If the thickness of the hard coat layer 6 exceeds 30 μm, the hard coat layer 6 may be easily cracked by repeatedly bending the optical film 1, and the flexibility may be deteriorated. Therefore, in order to achieve both surface hardness and flexibility, it is preferable to set the thickness of the hard coat layer 6 within the above range.

[0024] The optical film 1 according to this embodiment includes a hard coat layer 6 having both structural units derived from organic functional groups and inorganic structural units formed of siloxane bonds on a polyimide substrate 5, and therefore the hard coat layer 6 has flexibility derived from the organic structural units and surface hardness derived from the inorganic structural units. Therefore, the optical film 1 according to this embodiment is suitable as a protective film for a display device (mobile terminal) having a foldable display screen.

[0025] The optical film 1 according to the present embodiment may be used as a display member for forming a display device. Examples of the display member include a configuration in which an adhesive is laminated on the back surface (the surface opposite to the hard coat layer 6) of the substrate 5 of the optical film 1, a configuration in which another resin film is bonded to the back surface of the substrate 5 of the optical film 1, and a configuration in which a circularly polarizing plate is bonded to the back surface side of the substrate 5 of the optical film 1. EXAMPLES

[0026] Examples of the present invention will now be described in detail.

[0027] (material) A polyimide film having a thickness of 50 μm was used as the substrate, and the following composition was used as the coating liquid for forming the hard coat layer. <Coating liquid for forming hard coat layer 1: organic compound type> A base material containing 30 parts by weight of urethane acrylate, 9 parts by weight of dimethyl carbonate, and 9 parts by weight of an acrylic acid ester compound was mixed with 2 parts by weight of a radical polymerization initiator and 50 parts by weight of a solvent (a mixed solvent of methyl acetate, dimethyl carbonate (DMC), methyl isobutyl ketone (MIBK), and polyethylene glycol monomethyl ether (PGME)) to prepare coating liquid 1 for forming a hard coat layer. <Coating liquid 2 for forming hard coat layer: inorganic compound type> Coating liquid 2 for forming a hard coat layer was prepared by mixing a base material containing 28 parts by weight of urethane acrylate and 20 parts by weight of an inorganic dispersion such as silica or alumina with 2 parts by weight of a radical polymerization initiator and 50 parts by weight of a solvent (a mixed solvent of methyl acetate, DMC, and MIBK). <Coating liquid 3 for forming hard coat layer: organic-inorganic composite compound type> Coating liquid 3 for forming a hard coat layer was prepared by mixing 48 parts by mass of a polysiloxane having a T unit having a 2-(3,4 epoxy)cyclohexylethyl group per silicon atom as a constituent unit, 2 parts by mass of a radical polymerization initiator, and 50 parts by mass of a solvent (a mixed solvent of ethyl acetate and MIBK). <Coating liquid 4 for forming hard coat layer: organic-inorganic composite compound type> Coating liquid 4 for forming a hard coat layer was prepared by mixing 48 parts by mass of a polysiloxane having a T unit having a 2-(3,4 epoxy)cyclohexylethyl group per silicon atom as a constituent unit, 2 parts by mass of a cationic polymerization initiator, and 50 parts by mass of a solvent (a mixed solvent of ethyl acetate and MIBK).

[0028] (Examples 1 to 3) Using a bar coater, a hard coat layer-forming coating liquid shown in Table 1 was applied to one side of the substrate in a thickness such that the hard coat layer after curing would have the thickness shown in Table 1. The coating film was dried in a drying oven at 40 to 100°C for 30 to 60 seconds to remove the solvent. Thereafter, the coating film was cured by irradiation with ultraviolet light, and then heated at 100°C for 2 hours (post-heat treatment) to produce the optical films according to Examples 1 to 3.

[0029] (Comparative Examples 1 to 6) Optical films according to Comparative Examples 1 to 6 were produced in the same manner as in Examples 1 to 3, except that no post-heat treatment was carried out after the coating film was cured by UV irradiation.

[0030] The pencil hardness, bending property, and curl were evaluated for the optical films according to Examples 1 to 3 and Comparative Examples 1 to 6. The evaluation methods and evaluation criteria were as follows.

[0031] <Pencil hardness> The pencil hardness of the hard coat layer surface was measured using a pencil scratch tester (HA-301, Tester Sangyo Co., Ltd.) based on JIS K5600 (load of 4.9 N). When the measured pencil hardness was 7H or more, the surface hardness was determined to be sufficient.

[0032] <Flexibility> The bending property was evaluated using a U-shaped no-load bending tester manufactured by Yuasa System Co., Ltd. An optical film sample cut to 80 mm (machine direction) x 30 mm (width direction) was attached to a measuring jig and subjected to a repeated bending test 200,000 times with the hard coat layer on the inside. After the test, the bent portion was observed visually and under a microscope to see if there was any change in the appearance of the hard coat layer. If there was no damage, it was rated as OK, and if any damage such as cracks was observed, it was rated as NG.

[0033] <Curl> The optical film was cut to a size of 50 mm (machine direction) x 150 mm (width direction), and the cut sample was placed on clean paper laid on a flat workbench (see Figure 3). The distance A between both ends of one short side of the placed sample and the distance B between both ends of the other short side were measured, and the average value of distances A and B was used as the curl evaluation value. When the curl evaluation value was 18 mm or more, it was determined that curling was suppressed. When the curl was large and the sample was curled into a cylindrical shape, the diameter of the cylindrically curled sample was used as the evaluation value.

[0034] Table 1 shows the materials for the hard coat layer, the curing methods, and the thicknesses of the hard coat layers in Examples 1 to 3 and Comparative Examples 1 to 6, as well as the evaluation values ​​of the pencil hardness, flexibility, and curl.

[0035] [Table 1]

[0036] The optical films according to Examples 1 to 3 were excellent in surface hardness and flexibility, and had properties suitable for a protective film for a foldable display device. Moreover, the optical films according to Examples 1 to 3 were confirmed to have almost no curling and to have excellent mechanical suitability in the manufacturing process.

[0037] In contrast, the optical films according to Comparative Examples 1 and 2 had inferior surface hardness compared to Examples 1 to 3. Furthermore, as can be seen from the comparison between Comparative Examples 1 and 2, by increasing the thickness of the hard coat layer made of an organic compound, the pencil hardness could be improved, but the flexibility was reduced and curling also worsened.

[0038] In addition, the optical films according to Comparative Examples 3 and 4 had a high surface hardness comparable to that of the Examples due to the hard coat layer formed using an inorganic compound, but had insufficient flexibility and curled significantly.

[0039] The optical films according to Comparative Examples 5 and 6 used the same organic-inorganic composite material (polysiloxane) as in the Examples, but the hard coat layer was cured by radical polymerization, and as the curing proceeded rapidly, curling increased. [Industrial Applicability]

[0040] The present invention can be used as a protective optical film to be provided on the outermost surface of a display device, and is particularly suitable as an optical film for a display device having a foldable display screen. [Explanation of symbols]

[0041] 1 Optical film 2. Resin film 3 Circular polarizer 4 Display Panel 5 Base material 6 Hard Coat Layer

Claims

1. An optical film having a structure in which a hard coat layer is laminated on a polyimide substrate (excluding those including layers other than these two layers). the hard coat layer is made of a cured film of a composition containing a resin component and a polymerization initiator (excluding those containing a cured product of a (meth)acrylate compound); the resin component is made of a polysiloxane having a 2-(3,4 epoxy)cyclohexylethyl group and does not contain any polymerizable component other than the polysiloxane having a 2-(3,4 epoxy)cyclohexylethyl group; the polymerization initiator is a thermal cationic polymerization initiator or a photo cationic polymerization initiator, The thickness of the substrate is 50 to 80 μm, The thickness of the hard coat layer is 5 to 30 μm, The optical film is cut into a rectangle having a short side of 50 mm and a long side of 150 mm, and when the cut sample is placed on a flat surface, the average value of the distance between both ends of one short side and the distance between both ends of the other short side is 18 mm or more.

2. A display member comprising the optical film of claim 1.

3. A display device comprising a circular polarizing plate and the optical film according to claim 1 provided on a display panel.

4. The display device according to claim 3 , further comprising a resin film provided between the circular polarizing plate and the optical film.

Citation Information

Patent Citations

  • Apparatus for separating and purifying liquid

    JP1983081414A

  • Circularly polarizing plate with antireflection layer and image display device

    JP2012027322A

  • Laminate and image display device

    JP2020160137A

  • Composition for Forming Hard Coating Layer, Preparation Method of Hard Coating Film, and Hard Coating Film Prepared Using the Same

    US20200062991A1

  • Hard coat film, article provided with hard coat film, and image display apparatus

    WO2019207957A1